Mineral Liberation Studies Of Complex Sulphide Gold Ore From Pahang, Malaysia - Rosli, Mohamad Haikal (Universiti Sains Malaysia, 2018)
In the study of mineral liberation of complex sulphide gold ore in Pahang, Malaysia, raw sample from Selingsing Gold Mine Manager is used for analysis. The Selinsing district is famous with the occurrence of gold ore near the Central Belt of Peninsular Malaysia. The objective of this study is to study the mineral characterisation and composition of complex sulphide gold ore in Pahang, Malaysia. The mineral identification and quantification were carried out using the XRD while the mineral composition is determined using the XRF analysis. Before the XRF analysis, loss on ignition of the sample need to be determined first. The LOI value is 3.46%. The LOI value means that the sample contain low amount of organic matters. From the XRF analysis, the sample mostly consist of Silicon Oxide which is Quartz mineral with the value of 32.73% and the second most is Aluminium Oxide with the average value of 10.05%. The morphological study of the sample was done through the study of polished section using the SEM/EDX and optical microscope. The structure of the polish sample are mostly irregular shape and flaky while loose bulk sample only look flaky grain under the SEM/EDX. The lightest coloured grain is considered as gold, Au since gold is the heaviest element in the Periodic Table. Iron (Fe) and Copper (Cu) are quite hard to differentiate using the SEM since their atomic weight is almost the same thus the grey colour intensity of the two element almost the same. To differentiate them, EDX is needed. Lastly, the mineral liberation analysis is done using the Image J software. The highest value of mineral liberation stays about 20% at 150 μm size fraction.